2019
DOI: 10.1021/acs.jpcc.9b01520
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Impact of Defects on Catalytic CO Oxidation of LaFeO3-Supported Rh, Pd, and Pt Single-Atom Catalysts

Abstract: Understanding the intrinsic catalytic properties of perovskite materials can accelerate the development of highly active and abundant complex oxide catalysts. Here, we performed a first-principles density functional theory study combined with a microkinetics analysis to comprehensively investigate the influence of defects on catalytic CO oxidation of LaFeO 3 catalysts containing single atoms of Rh, Pd, and Pt. La defects and subsurface O vacancies considerably affect the local electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 59 publications
2
24
0
Order By: Relevance
“…Low-temperature catalytic conversion of carbon monoxide (CO) to carbon dioxide (CO 2 ) via oxidation is one of the key parts of several chemical processes of industrial significance, including CO removal by preferential oxidation in H 2 -rich stream for fuel cell applications, 1−4 control of toxic contents in the exhaust gas from combustion engines and automobiles, 5,6 and so forth. Though noble-metal catalysts, including Pt, 7−15 Pd, 16−23 Rh, 24,25 Au, 26−29 Ir, 30,31 and so forth, are highly active in CO oxidation, they are expensive, and their performances are strongly dependent on the reaction conditions. 9,12,32 Considerable attention has been devoted to develop novel CO oxidation catalysts efficient at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Low-temperature catalytic conversion of carbon monoxide (CO) to carbon dioxide (CO 2 ) via oxidation is one of the key parts of several chemical processes of industrial significance, including CO removal by preferential oxidation in H 2 -rich stream for fuel cell applications, 1−4 control of toxic contents in the exhaust gas from combustion engines and automobiles, 5,6 and so forth. Though noble-metal catalysts, including Pt, 7−15 Pd, 16−23 Rh, 24,25 Au, 26−29 Ir, 30,31 and so forth, are highly active in CO oxidation, they are expensive, and their performances are strongly dependent on the reaction conditions. 9,12,32 Considerable attention has been devoted to develop novel CO oxidation catalysts efficient at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…To describe the effect of the exchange-correlation and the on-site Coulomb interaction, the Perdew, Burke, and Ernzerhof (PBE) functional [50] with the Hubbard + U correction was used. The effective U value for the Fe 3 d orbital was set to be 4 eV [51] . The weak van der Waals (vdW) interactions were described by the DFT + D3 method [52] .…”
mentioning
confidence: 99%
“…For example, DFT calculations on M 1 /LaFeO 3 (M=Rh, Pd, Pt) revealed that a M 1 /LaFeO 3 catalyst with a La defect demonstrated more optimized CO/O 2 adsorption and therefore better catalytic performance. [102] Among LaFeO 3 Rh, Pd, and Pt single atoms, Pd 1 / LaFeO 3 with a La defect presents the highest reactivity. A similar strategy was also applied to guide the design of M 1 / LaBO 3 (M=Rh, Pd, Pt; B=Mn, Fe, Co, Ni).…”
Section: Theoretically Guided Sac Designs With Different Supportsmentioning
confidence: 96%
“…First‐principle calculations were performed recently on perovskite‐supported SACs to guide their design. For example, DFT calculations on M 1 /LaFeO 3 (M=Rh, Pd, Pt) revealed that a M 1 /LaFeO 3 catalyst with a La defect demonstrated more optimized CO/O 2 adsorption and therefore better catalytic performance [102] . Among LaFeO 3 Rh, Pd, and Pt single atoms, Pd 1 / LaFeO 3 with a La defect presents the highest reactivity.…”
Section: Sacs For Co Oxidationmentioning
confidence: 99%